2018
DOI: 10.1186/s12989-018-0257-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic components of diesel exhaust particles induce pro-inflammatory responses in human endothelial cells through AhR dependent pathway(s)

Abstract: BackgroundExposure to traffic-derived particulate matter (PM), such as diesel exhaust particles (DEP), is a leading environmental cause of cardiovascular disease (CVD), and may contribute to endothelial dysfunction and development of atherosclerosis. It is still debated how DEP and other inhaled PM can contribute to CVD. However, organic chemicals (OC) adhered to the particle surface, are considered central to many of the biological effects. In the present study, we have explored the ability of OC from DEP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 75 publications
12
65
0
Order By: Relevance
“…In contrast, no attenuation was observed at lower concentrations (100 µg/mL), with lower cytokine responses. This indicates that, at least in the present case, ROS‐dependent mechanisms were predominately a high‐concentration phenomenon, as recently also observed for DEP, possibly acting by exacerbating the effects of other particle‐/NP‐induced pathways. In further support of this, even at the highest Si50 concentrations, ROS inhibition only exerted partial reductions in the cytokine response, suggesting a combination of ROS‐dependent and ROS‐independent mechanisms.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, no attenuation was observed at lower concentrations (100 µg/mL), with lower cytokine responses. This indicates that, at least in the present case, ROS‐dependent mechanisms were predominately a high‐concentration phenomenon, as recently also observed for DEP, possibly acting by exacerbating the effects of other particle‐/NP‐induced pathways. In further support of this, even at the highest Si50 concentrations, ROS inhibition only exerted partial reductions in the cytokine response, suggesting a combination of ROS‐dependent and ROS‐independent mechanisms.…”
Section: Discussionsupporting
confidence: 82%
“…Up-regulation of HO-1, MMP-1 and -9 may possibly be related to downstream effects of earlier cytokine responses. Similarly, exposing the same 3D tri-culture to DEP, MMP-1 was only induced at the latest time point [53].…”
Section: Discussionmentioning
confidence: 99%
“…The 3D tri-culture model, established as described by Klein and co-workers [43,44], consisted of three different cell-types, A549 epithelial lung cells, PMAdifferentiated THP-1 cells, and EA.hy 926 endothelial cells (from the American Type Culture Collection, Manassas, VA, USA), and has been used by us in a previous study [53]. The Ea.hy 926 cells were maintained in DMEM + Glutamax, with HEPES buffer (DMEM) and 10% FBS.…”
Section: Culturing Of Cells; Building the 3d Tri-culture And Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Endotoxins can also stimulate localized or systemic inflammation via the activation of pattern recognition receptors [35]. Several studies reported that the biological and chemical components of particulate matter have synergistic pro-inflammatory effects [36][37][38][39][40].Some researchers have proven that particulate matter is a key cause of cardiovascular morbidity and mortality [41]. Animal experiments have also confirmed that particulate matter exposure triggers inflammation and oxidative stress, which may cause lung and heart injure [42,43].…”
Section: Discussionmentioning
confidence: 99%